Validação do Questionnaire on Resources and Stress - Short Form (QRS-F) - Zanfelici, Tatiane Oliveira (2013)
Family members of people with disabilities may be exposed to various stressors, among them the disability itself, becoming potential targets of stress. In this context, several models have been designed for the study of stress, among which highlights the Cognitive Assessment and the ABC-X, which comprise the coping strategies as a way to mediate the perception of stressors. Researches conducted with several family members have pointed out that the constant stress can lead to more roughness family relationships, and fewer opportunities for stimulation of child development, which contribute to enhance family relationships with any child, including those with disabilities. For the evaluation of the parental stress variable, studies show the use of different instruments, including the Questionnaire on Resources and Stress - QRS-F which stand out for being directed especially to families of children with disabilities and chronic illnesses. Given the above, this study proposed two objectives: 1) the cross-cultural adaptation of the QRS-F, since the translations available in Brazil do not have this treatment, or definitely modified the structure of the questionnaire, 2) a study of the evidence of psychometric validity of the instrument . The first study involved five independent translators, five professionals on the thematic area of the instrument and seven relatives of people with autism. The questionnaire underwent procedures of translation and retranslation, as well translations adjustments, resulting in altered or partially altered. The evaluation of the expert committee regarding the relevance of the questions in the conceptual levels, language and experimental indicated substantial kappa at all levels of assessment, indicating that the translation was adequate for the pilot application. The second study involved 57 mothers, fathers, grandparents and sister of children with and without various disabilities. Their analyzes showed significant correlations with the measure of stress obtained by Symptom Inventory Lipp Stress and the instrument that assessed coping resources, the Coping Strategies Inventory, indicating associations with the dimensions of the QRS-F Parental Problems, Pessimism and Physical Incapacity . The reliability coefficient obtained by the proof of Kuder-Richardson pointed a ratio considered adequate (KR-20 = .64). The test criterion validity indicated higher scores related to the dimension of the QRS-F called Pessimism, when compared groups of respondents relatives of people with and without various disabilities. It was considered that this version of the QRS-F, now called Questionnaire of Resources and Stressors, possesses the attributes necessary to be considered a valid tool in research in the area of parental stress in Brazil. It is suggested to do a further study, covering a broader sample of respondents, which allow the realization of more sophisticated analyzes, but indispensable for the consolidation of this instrument.